Manajemen Supervisi Akademik Kepala Sekolah dalam Meningkatkan Kinerja Guru SD Se-Kecamatan Grogol, Kota Cilegon - Inti Hujah; Ifa Hafiroh; Ramdan; Sudaryono (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
Principal academic supervision management is a crucial factor in improving elementary school teacher performance amid the increasing demands for educational quality and digital transformation in the Grogol District, Cilegon City. The background of the study indicates persistent issues in teacher performance, including suboptimal lesson planning, less innovative teaching methods, and limited integration of educational technology. The research problem is formulated as how principals manage academic supervision to enhance teacher performance through planning, implementation, evaluation, and follow-up processes. This study employs a qualitative case study approach involving eleven public elementary schools. The findings reveal that academic supervision is conducted systematically, collaboratively, and continuously through classroom observations, reflective discussions, workshops, and On-the-Job Training supported by the Academic Learning System. The results indicate a 15 percent improvement in teacher performance, increasing from 75 to 95, as well as an 80 percent improvement in school learning achievement. The study concludes that integrated, collaborative, and technology-based academic supervision management significantly enhances teacher professionalism. The novelty of this research lies in the development of a digital-collaborative supervision model that integrates teacher participation, continuous professional development, and real-time digital monitoring systems to ensure more effective, efficient, and measurable teacher performance management. Supporting factors include principal commitment, teacher openness, collaborative school culture, and technological support. In contrast, the main obstacles include time constraints, administrative workload, and variations in teacher competence. The findings imply that academic supervision should be managed as adaptive, participatory, and sustainable professional development oriented toward continuous improvement of learning quality in Indonesian elementary schools, serving as a reference for developing a more effective, systematic, and sustainable digital-collaborative supervision model.